A compactness result for non-local unregularized gradient flow lines - Albers, Peter; Frauenfelder, Urs; Schlenk, Felix (Arxiv, 2018)
We prove an abstract compactness result for gradient flow lines of a non-local unregularized gradient flow equation on a scale Hilbert space. This is the first step towards Floer theory on scale Hilbert spaces.
Gesehen am 18.02.2019